Du Bellay and the Catchword: From L’Olive (1549) to Les Regrets (1558) - Conley, Tom (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
Joachim Du Bellay, a poet of contradiction, is known in his later verse for mastering a sculpted and “cold” style of writing. This article proposes that in conjunction with a unique typography and formatting of the poems in their first editions, catchwords (or réclames), seemingly isolated and fragmentary marks at the end of gatherings of signatures, punctuate the verse and, now and again, become a function of its force. Appearing as they do and where they do, catchwords invoke what poet René Char called a parole en archipel (words comprising an archipelago and of an originary calling), and what Maurice Blanchot referred to as a parole de fragment (speech of fragment) or a parole morcelée (shattered speech). Of uncommonly modern appeal, catchwords—intermediaries, unique spatial signs—are vital elements in the design, impact, and consequence of collections that run from L’Olive and the Recueil de poesie (1549) to Fédéric Morel’s handsome and carefully formatted editions of Le Premier livre des Antiquitez de Rome and Les Regrets (1558).